Free Composition - Schenker, Heinrich 1868-1935; Oster, Ernst (New York London Longman, 1979)
Free Composition was the third in Heinrich Schenker's (1868-1935) series "New Musical Theories and Fantasies". The two preceding it were "Harmony" (1906) and "Counterpoint" (volume I in 1910 and volume II in 1922). While every undergraduate student in music has taken courses on harmony and counterpoint, Schenker's views are not designed as pedagogical tools to teach the rudiments of musical grammar. Yes, they do cover some of the same ground, but Schenker was always after a deeper interpretation of the composition and revealing the composer's art than as something merely to be explained, generally applied, and played with only surface facility.Unfortunately, Schenker died before this, his most profound work, was fully prepared and published. The first German edition was hastily put together and published hastily. Oswald Jonas corrected, added notes and edited its second edition in 1955. The present English edition and translation was done by Ernst Oster and was published in 1979 to much justified acclaim by Longman (with assistance from the American Musicological Society). Oster added many clarifying notes, and created an English version that is even clearer than the original German. Schenker's writing, after all, can be cryptic, inconsistent, and obscure. Carl Schachter said in his 1981 review of this edition that he suspected "that German readers who are fluent in English will consult `Free Composition', partly because of its excellent notes but also because, as Allen Forte remarks in his Introduction, The English version is often clearer than the original." Unfortunately, Oster died in 1977 and John Rothgeb prepared the manuscript for its actual publication.What does Schenker say in this book? It is his most penetrating look at aspects of the ways in which masterworks not only use the superstructure of the "fundamental line" as background, but have motivic connections between the various levels of middleground and foreground (the last of which is the surface of the music). No, this isn't a scientific or mechanical process that a technician could use to crank out music analyses. It is a way of expressing one's interpretation of the composition and sharing what you hear with others. Schenker's views have often caused controversy. His own prickly, elitist, nationalistic, and sometimes insulting prose has not helped his cause. However, there are many wonderful musical scholars that have found great insight through these methods and their usefulness is too great to ignore.Some have been accused of turning every ink stain by Schenker into musical scripture, but that goes much too far. Others have adopted a style of analytical notation that appears to look like Schenker's, but without any formal connection to the theorist's usage or thought. This is a bad thing. How do you avoid becoming an unthinking acolyte or a blithering scribbler? By careful study of Schenker's writings including "Harmony" and "Counterpoint". You don't start with this book all by itself. This assumes that the reader has a good idea of Schenker's views on counterpoint, voice leading, and the role of harmony and in the "composing-out" process.The musical examples are not like the complete analyses you will find in "Five Graphic Analyses", but are provided as specific examples to illustrate a point Schenker is making when discussing levels in composition. I think this book is a great treasure and I commend it to anyone who loves music enough to want to dig into it at deeper level. The rewards you reap will be great. It will take real effort, time, and seeking out a good teacher to answer your questions, but it will be worth it.
Keywords: 20th Century (1901-2000); Composing; Music theory; Method